Image Analysis Studies for Phase Transitions of Ferroelectric Liquid Crystals. (21st October 2012) - Sastry, S. Sreehari; Rao, B. Gowri Sankara; Mahalakshmi, K. B.; Mallika, K.; Rao, C. Nageswara; Tiong, Ha Sie
Abstract : Phase transition temperatures of ferroelectric liquid crystals ((S)-(-)-2-methylbutyl 4′-(4 ″ - n -alkanoyloxybenzoyloxy) biphenyl-4-carboxylates (where n = 16 and 18)) are studied through two techniques of image analysis. One is a statistical method, applied to compute the statistical parameters from the textures of each sample and the other, computation of Legendre moments being applied as image moment analysis, both of which are considered as a function of temperature. The textures of the samples are recorded with the polarizing optical microscope (POM) attached to the hot stage and high resolution camera. The phase transition temperatures of samples are inferred by the abrupt changes in the computed parameter values. The results obtained from the present methodology are in good agreement with those published in earlier literature done by the different techniques, like differential scanning calorimetry (DSC).